The Impact Of Workload, Job Satisfaction And Job Burnout On Turnover Intention Nurses In The Public Hospital - Lestari, Fuza; Amalia, Fina; Sunimah (Indonesian Journal of Business Analytics, 2024)
This research aims to determine the influence of workload, job satisfaction, and work fatigue on nurse turnover intention. This research used quantitative methods with a population of nurses at regional general hospitals using a non-probability purposive sampling technique involving 150 respondents out of a total of 288 nurses. The analysis technique was carried out using multiple regression analysis with SPSS 26. Data was collected through a questionnaire using a Likert scale measurement instrument. The results of this study indicate that workload has an insignificant effect on the intention to change jobs. Meanwhile, job satisfaction has a negative and significant influence on turnover intention. Apart from that, job fatigue has also been proven to have a negative and significant influence on the intention to change jobs. Furthermore, there is a simultaneous influence of the variables workload, job satisfaction, and job fatigue on the intention to change jobs.